2012
DOI: 10.1007/s00299-011-1219-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of seven class III peroxidases induced by overexpression of the agrobacterial rolB gene in Rubia cordifolia transgenic callus cultures

Abstract: Here, seven new class III peroxidase genes of Rubia cordifolia L., RcPrx01-RcPrx07, were isolated and characterized. Expression of the Prx genes was studied in R. cordifolia aerial organs as well as in cells transformed with the rolB and rolC genes of Agrobacterium rhizogenes and cells transformed with the wild-type A. rhizogenes A4 strain. In rolC- and rolB-transformed cells, the rol genes were expressed under the control of the 35S promoter, whereas in A. rhizogenes A4-transformed cells the rol genes were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…Another feature of rolB is that the gene strongly activates expression of the extracellular class III peroxidase genes and enhances total peroxidase activity in transformed cells [61]. This effect is dose-dependent and is observed in all rolBexpressing plant species studied.…”
Section: Ros Homeostasis and Expression Of Antioxidant Genesmentioning
confidence: 97%
“…Another feature of rolB is that the gene strongly activates expression of the extracellular class III peroxidase genes and enhances total peroxidase activity in transformed cells [61]. This effect is dose-dependent and is observed in all rolBexpressing plant species studied.…”
Section: Ros Homeostasis and Expression Of Antioxidant Genesmentioning
confidence: 97%
“…Likewise, rolC diminished the rolB-induced high sensitivity to auxin in transformed cells (Maurel et al, 1991) and the severity of rolB-induced phenotypes (Capone et al, 1989;Vanaltvorst et al, 1992). Recently, a contrasting difference between the action of rolB and rolC on class III peroxidase gene expression has been demonstrated (Veremeichik et al, 2012). Although overexpression of a single rolB gene caused dramatic up-regulation of R. cordifolia class III peroxidase genes, the effect of the rolC gene on peroxidase transcript abundance was minimal.…”
Section: Combined Effect Of the Rolb And Rolc Genesmentioning
confidence: 99%
“…It was previously shown that the majority of antioxidant genes studied, including those encoding the Cu/Zn superoxide dismutases, catalases, ascorbate peroxidases and class III peroxidase genes, were coordinately upregulated in rolB-expressing cells. 5,19 RolB permanently sustains an active anti-oxidative environment in transformed cells and simultaneously maintains their normal redox balance, providing physiological conditions for adaptation to external oxidative stress. 5 While the cellular conditions leading to PCD induction are linked with an imbalance in redox status, 20 this function of RolB may be important for PCD prevention.…”
Section: -11mentioning
confidence: 99%